The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1053/j.semperi.2017.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Improving hospital quality to reduce disparities in severe maternal morbidity and mortality

Abstract: Significant racial/ethnic disparities in maternal morbidity and mortality exist in the United States. Black women are three to four times more likely to die a pregnancy-related death as compared with white women. Growing research suggests that hospital quality may be a critical lever for improving outcomes and narrowing disparities. This overview reviews the evidence demonstrating that hospital quality is related to maternal mortality and morbidity, discusses the pathways through which these associations betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(81 citation statements)
references
References 59 publications
1
74
1
Order By: Relevance
“…However, unfamiliarity should not breed contempt. Basic principles of safety and quality were relatively unknown in the health care community even a few years ago; in a short time, they have increasingly pervaded maternity care and their adoption has been associated with improved outcomes . Although some disparity in outcomes may arise because racial and ethnic minority women are more likely to receive care in different hospital settings (ie, disparities resulting from interhospital differences), this difference in site of care cannot explain the extent of disparities that exist, and evidence exists for racial and ethnic disparities within individual hospitals as well (ie, intrahospital differences); yet, whether the disparities are rooted in within‐ or between‐hospital differences, many of the remedies are the same.…”
Section: Discussionmentioning
confidence: 99%
“…However, unfamiliarity should not breed contempt. Basic principles of safety and quality were relatively unknown in the health care community even a few years ago; in a short time, they have increasingly pervaded maternity care and their adoption has been associated with improved outcomes . Although some disparity in outcomes may arise because racial and ethnic minority women are more likely to receive care in different hospital settings (ie, disparities resulting from interhospital differences), this difference in site of care cannot explain the extent of disparities that exist, and evidence exists for racial and ethnic disparities within individual hospitals as well (ie, intrahospital differences); yet, whether the disparities are rooted in within‐ or between‐hospital differences, many of the remedies are the same.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, 37.3% of black women gave birth at hospitals that had the highest rates of severe maternal morbidity. Howell et al also considered how hospital‐level variables predicted severe maternal morbidity. They found that hospitals with level 3 or 4 nurseries, private ownership, teaching status, and very high birth volumes had lower risk of severe maternal morbidity events.…”
Section: Health Care System Insights and Approaches Regarding Racialmentioning
confidence: 99%
“…Following their analyses, these researchers recommended that all low‐performing hospitals in the United States make changes that range from structural alterations (staff‐to‐patient ratios, time of day staffing, qualifications of staff) to organizational updates (audit and feedback on clinical practices of providers, use of quality improvement bundles, hospital culture improvements) to increase quality and thereby reduce racial disparities in maternal morbidity and mortality . For example, patient safety bundles could be used to help reduce racial disparities in maternity outcomes by standardizing treatment for common emergencies such as shoulder dystocia and postpartum hemorrhage . The Council on Patient Safety in Women's Health Care, a multidisciplinary team of health care providers, public health professionals, and cross‐sector stakeholders, has published an assortment of maternity care bundles that are designed to reduce peripartum racial and ethnic disparities.…”
Section: Health Care System Insights and Approaches Regarding Racialmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common preventable factors include provider-related factors (e.g., delays in diagnosis or treatment) [5,6]. There is a growing body of work highlighting the potential influence of the health care system and standards of care on maternal health outcomes [7][8][9][10] Nurses provide obstetrical care across the U.S. healthcare continuum, including in outpatient clinics and hospitals. Obstetrical nurses monitor for maternal condition changes in the outpatient setting and are responsible for coordinating timely care during obstetrical emergencies.…”
Section: Introductionmentioning
confidence: 99%